SCIENTIFIC CONTRIBUTION OF PROFESSOR MAKSIMENKO PAVLO TIKHONOVICH - P.M. Skripnikov; T.P. Skripnikova; Т.А. Khmil (Український стоматологічний альманах)
The contribution of Prof. P.T. Maksymenko in the development of topical issues of prevention and treatment of major dental diseases was enormous. Particular attention is paid to published manuals on allergology in dentistry, medical pathology, difficulty and errors in the diagnosis of diseases of the mucous membrane of the oral cavity.